2014
DOI: 10.1038/sj.bdj.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

The development of a designated dental pathway for looked after children

Abstract: The dental care pathway had a beneficial impact on the dental access and experiences of children who used it, promoted better interagency working and facilitated record keeping. These findings call for extension of the service to a wider population to allow further evaluation of its impact and efficacy in different regional areas and contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…For example, immunisation rates are far lower than in the general population . The high rates of dental health problems in our sample echo single small sample studies from the UK, even though there is a dearth of research in this field .…”
Section: Discussionmentioning
confidence: 45%
“…For example, immunisation rates are far lower than in the general population . The high rates of dental health problems in our sample echo single small sample studies from the UK, even though there is a dearth of research in this field .…”
Section: Discussionmentioning
confidence: 45%
“…A dental hospital‐based paediatric liaison nursing service was shown to promote integrated multidisciplinary working with public health nurses, facilitating assessment of harm to children and prompting additional referrals to social services 27 . More recently, examples of innovative practice in organisational and administrative support have been published, including model referral pathways for vulnerable children to facilitate their dental care and streamline the additional workload 28–31 …”
Section: Discussionmentioning
confidence: 99%
“…Much of the knowledge about the uptake of health services by LAC comes from studies on mental health, and we know less about the uptake of interventions which prevent or treat common physical health problems 7 8. While oral health problems and dental service access have been recognised as issues among LAC,9 the epidemiological research is limited. There is only one previous study from Scotland which looked at this issue: a survey of 96 young people in and leaving care placements which found that half the respondents had not visited the dentist in the past year 7.…”
Section: Introductionmentioning
confidence: 99%